Scrapt Waste Tire as an Additive in Asphalt Pavement for Road Construction - Tomas Ucol Ganiron Jr (International Journal of Advances in Applied Sciences, 2013)
This experiment study aimed to use of the waste tires in asphalt mixture as additive. Research has shown that scrap waste tire can be partial replacement by 2% total weight of aggregate retained in No. 4 sieve has an average performance. Characteristics compared to the standard eequirements conformable code. Moreover, the use of scrap waste tire would result in the reduction of waste. High stability of asphalt mixture can be made and the incorporation of admixture or substitute to improve the properties of the mixture. Test result of specimens indicates the stability, and bonding strength of properties, and different reaction when gradation and scrap tire contents have varied. Marshall test having an appropriate workable mixing and right temperature gave sufficient compressive strength and lessen its flow or it deformation under a certain loads.